(3JUGfja CHj HcQ CMeO Hf Ydi Hf KGHJ GdNWjH GdHZOGOis - (3eMeO UGOb Hf GdSjO Gejf GdeGdMs
(3ChdgG (B:s
(3cJGH JGQjN eOjfI GdSdGe hGNHGQ eMOKjgG hPcQ bWGgG GdYdeGA ef ZjQ CgdgG s
(3BNQgG (B:s
(3hcGf jPgH Edi ePgH CHj GdMSf GdGTYQi ai GdCUhd hcGf KbI MGaXkG ced GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3GfXQg eY GdeNWhW (B183 (3ef faS GdHYKIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJGQjNs